An Application Of Labour Law In The Human Resource Development Process - Muridha Hasan; Lusi Tutur Mulai; Saddam Hasrul; Rila Maufira (Jurnal Scientia, 2024)
This research was conducted with the aim of finding out how companies improve the quality of human resources in Indonesia and how legal protection is for Human Resources in Indonesia. Increasing employee performance will bring progress to the company, employees who have good performance are needed who can work effectively and efficiently. The data source is primary, namely the results of interviews with personnel managers regarding the principles and basis of transfers. Another source of data is secondary data in the form of documents, reports, books, research journals, articles and related scientific magazines. Data collection techniques through interviews and documentation. The data analysis technique uses descriptive-qualitative.